Aldehyde Dehydrogenase 2 Protects Against Lipopolysaccharide-Induced Myocardial Injury by Suppressing Mitophagy - Ji, Wenqing; Wan, Tiantian; Zhang, Fang; Zhu, Xiaomei; Guo, Shubin; Mei, Xue (Frontiers in Pharmacology, 2021)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Sepsis-induced circulatory and cardiac dysfunction are associated with high mortality rates. Mitophagy, a specific form of autophagy, is excessively activated in lipopolysaccharide-induced myocardial Injury. Our present study investigated whether aldehyde dehydrogenase 2 (ALDH2) regulates mitophagy in septic myocardial anomalies. After LPS stimulation, cardiac dysfunction, inflammatory cell infiltration, biochemical indicators of myocardial cell injury, and cardiomyocyte apoptosis were ameliorated in mice by ALDH2 activation or overexpression. Moreover, ALDH2 activation or overexpression regulated mitophagy by suppressing expression of phosphatase and tensin homolog-induced putative kinase 1 (PINK1)/Parkin, thereby preventing 4-hydroxynonenal accumulation. Consequently, ALDH2 may protect the heart from LPS injury by suppressing PINK1/Parkin-dependent mitophagy.